Self-perception of aging among HIV-positive and HIV-negative participants in the Multicenter AIDS Cohort Study. Issue 7 (2nd July 2020) - Nieves-Lugo, Karen; Ware, Deanna; Friedman, M. Reuel; Haberlen, Sabina; Egan, James; Brown, Andre L.; Dakwar, Omar; Plankey, Michael
ABSTRACT: Self-perception of aging is an important predictor of quality of life. Therefore, we sought to examine self-perceptions of aging (age discrepancy and aging satisfaction) between HIV-positive and HIV-negative men in the Multicenter AIDS Cohort Study (MACS). We included 835 HIV-negative and 784 HIV-positive men aged 50 years and older who had completed a survey about age discrepancy and aging satisfaction from the "Attitude toward own aging" subscale of the Philadelphia Geriatric Center Morale scale. Multinomial generalized logit models were generated to assess self-perception of aging by HIV-status. Most of the participants self-identified as white, former smokers, and had completed high school. HIV-positive individuals reported higher prevalence of comorbidities than HIV-negative individuals. After adjusting for covariates, positive age discrepancy (older subjective age) was positively associated with being HIV-positive and having less than a high school education, depressive symptoms, diabetes, and medium and low aging satisfaction. Low aging satisfaction was associated with being a current and former smoker and having depressive symptoms, diabetes, and no age and positive age discrepancy. Being black had decreased odds of low aging satisfaction. These findings should inform health care professionals to promote positive views of aging in the assessment and management of HIV, depression, and diabetes.